Evaluation of Y2O3 as front layer of ceramic crucibles for vaccum induction melting of tial based alloys - Barbosa, J. (2005)
During the last decades titanium alloys were found to be valuable engineering materials for many different applications. Formerly used in critical applications like aerospace, aeronautic and military equipment, where the factor cost is not relevant, titanium alloys are finding now new and different markets. However, the development of such new markets will depend on an effective cost reduction of titanium parts, in order to achieve a selling cost suitable with its application in consumer goods. A possible solution to decrease production costs might be the use of traditional casting techniques to produce near net shape functional parts. During the last years, the authors have developed extensive research work on this field, and a new technique both for melting and moulding, using ceramic multi-layered crucibles and investment casting shells was developed. This paper presents some of the results obtained during that research work: Ti-48Al alloy were melted and cooled inside CaO, MgO and Y2O3 stabilized ZrO2 crucibles with inside layer of Y2O3. The chemical composition, hardness and microstructure at the metal-crucible interface, studied by secondary ion mass spectrometry, SEM/EDS and XRS are presented. On a second step, the same alloy was melted on the same crucibles, and poured into graphite moulds, and the crucibles wall was characterized by SEM/EDS and XRS.